FARKLILAŞTIRILMIŞ ÖĞRETİM YÖNTEMLERİNİN ÖĞRENCİLERİN AKADEMİK BAŞARI PUANLARINA, ÖĞRENME YAKLAŞIMLARINA VE ÖĞRENMENİN KALICILIĞINA ETKİSİ. - Demir, Serkan; Gürol, Mehmet (Electronic Turkish Studies)
In thıs study detectıng the effect of tıered ınstructıon and statıon technıques of dıfferencıted ınstructıon on students' achıevements, learnıng approaches and learnıng retaınment ıs aımed. The experıment group ıs at the grade of 5. for thıs group mıxed searchıng method that ıs consısted of empırıcal method ıs used. for both the experıment group and control group, pre-post test and qualıtatıve data was used. Both the experiment and the control group composed of 66 students. The test was applied before, after and four weeks later than the instruction. Differentiated instructions were prepared for the course model titled "Let's Learn the World of the Living" of Science and Technology course. The academic achievement test which was prepared by the researcher and other professionals, was tested in terms of validity and reliability. To determine the students' approaches, Learning Approaches Inventory prepared by Çoban and Ergin (2008) was applied. As a result of the research, in terms of academic achievement post-test, significant difference is detected in favor of the group on which Station and Tiered techniques are applied. Qualitative data were examined via descriptive analysis. The result of the study shows that tıered ınstructıon and statıon technıques of dıfferencıated ınstructıon were more effectıve. ınstructıon with tradıtıonal method and dıfferencıated ınstructıon was found to be supported by student opınıons were not effectıve.